2021
DOI: 10.2118/208580-pa
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment and Field Case Study on Oil/Natural Gas Explosion during High-Pressure Air Injection Process

Abstract: Summary Air injection techniques have been widely applied in oil fields, but the associated safety issue of natural gas (NG) and oil explosion has been of great concern. In this study, explosion experiments of different NG compositions were conducted under high-pressure and high-temperature conditions (up to 15 MPa and 373 K) to reveal the necessary conditions for gas explosion in the air injection process. The experimental results indicate that the lower flammability limits (LFLs) and upper fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Likewise, efforts should be made to sequester and manage the produced CO 2 . Perez et al, 2010 proposed a mineral carbonation approach for the ISC pilot project in the FPO, based on caustic byproducts (liquor and red mud) from alumina production. Additionally, EOR projects could be focused on other deposits where previous studies have indicated the technical feasibility of application, but because they did not have enough source of CO 2 they were not applied (e.g., reservoirs in the North Monagas area). CO 2 could also be injected into aquifers, in this sense feasibility studies have been carried out in deposits of the gas area of Anaco -Venezuela. , …”
Section: Discussionmentioning
confidence: 99%
“…Likewise, efforts should be made to sequester and manage the produced CO 2 . Perez et al, 2010 proposed a mineral carbonation approach for the ISC pilot project in the FPO, based on caustic byproducts (liquor and red mud) from alumina production. Additionally, EOR projects could be focused on other deposits where previous studies have indicated the technical feasibility of application, but because they did not have enough source of CO 2 they were not applied (e.g., reservoirs in the North Monagas area). CO 2 could also be injected into aquifers, in this sense feasibility studies have been carried out in deposits of the gas area of Anaco -Venezuela. , …”
Section: Discussionmentioning
confidence: 99%